DETERMINAN TAX AVOIDANCE DENGAN PERAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Dewi, Citra Cerya Mulya; Tohari, Amin; Sugeng (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to examine the effect of financial distress, profitability, firm size on tax avoidance with good corporate governance as a moderating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2019-2022 period. The sample was determined using a purposive sampling technique, obtained as many as 10 companies with 4 years of observation so that 40 observations were obtained. The analysis technique used Moderated Regression Analysis (MRA) which was tested with SPSS software version 23. The results of this study indicate that Financial Distress and Profitability have an effect on Tax Avoidance, while Firm Size has no effect on Tax Avoidance. Good Corporate Governance variables are not able to moderate the effect of Financial Distress, Profitability, and Firm Size on Tax Avoidance.